9-amino acid cyclic peptide-decorated sorafenib polymeric nanoparticles for the efficient in vitro nursing care analysis of hepatocellular carcinoma. (January 2021) - Hu, Yue; Yu, Dan; Zhang, Xiaoxia
Graphical abstract: Highlights: Designed and developed the sorafenib-surface decorated iRED nanoparticles. Sora-NPs and iRED@Sora-NPs shows excellent in vitro cytotoxicity against hepatocellular cancer cells. The cancer cells morphological examinations were investigated by various biochemical analyses. Further, the cell death mechanisms were explored by flowcytometry analysis. Abstract: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related mortality worldwide. Sorafenib acts as a potential anticancer agent, but it shows less aqueous solubility, so its clinical application is limited. In this present study, we developed Sora-surface decorated iRGD (small cyclic peptide motif (CRGDK/RGPD/EC)) nanoparticles (labelled Sora-NPs and iRGD@Sora-NPs, respectively) to enhance its aqueous formulation and improve the anticancer activity of Sora. The synthesized Sora-NPs and iRGD@Sora-NPs confirmed by various spectroscopies and electroscopic techniques. Sora-NPs and iRGD@Sora-NPs dramatically suppressed the proliferation of hepatocellular carcinoma cells (BEL-7402 and Huh-7) and showed low toxicity in MTT assays. Compared with free Sora and Sora-NPs, iRGD@Sora-NPs significantly induces the apoptosis in hepatocellular carcinoma cells. The morphological changes were evaluated via various biochemical staining techniques (AO-EB and nuclear staining). Further, the apoptosis mode of hepatocellular carcinoma cell death was confirmed via flow cytometry analysis. Furthermore, the Sora-NPs and iRGD@Sora-NPs promoted apoptotic manner of cell death by G2/M phase arrest. In this present study explained that iRGD@Sora-NPs as a safe and hopeful strategy for chemotherapeutics of hepatocellular carcinoma therapy and deserve further clinical evaluations.